Identification and validation of screening methods for assessment of the sheening potential of embedded oil in sediments - Sitler, Katherine, author; Scalia, Joe, advisor; Sale, Tom, advisor; Sutton, Sally, committee member (Colorado State University. Libraries, 2020)
Sediments impacted with petroleum hydrocarbons (oil) may sheen due to ebullition-driven transport or sediment disturbance. The goal of this project was to develop a screening method that can be deployed on a small autonomous watercraft that will provide a reliable indication of sheening potential of embedded oil in shallow sediments. Different potential probes and methods were explored to penetrate sediments and determine sheening potential. Preliminary probe identification focused on development of a standardized laboratory column to test different probes and penetration methods to determine which probe has the highest probability to generate a sheen. Column tests were performed that consisted of different combinations of five crude oil types and a control (no oil embedded), seven probe candidates, two types of oil deposits, two targeted sheen levels, and with or without embedded air. Based on the data collected, a direct push rod with water injection had the greatest potential to generate a sheen.